Pengaruh PDRB Perkapita, Populasi dan Partisipasi Angkatan Kerja Terhadap Kemiskinan di Pulau Sumatera: Perspektif Ekonomi Islam - Adinda, Delvira Rahma; Ghofur, Ruslan Abdul; Etika, Citra (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the influence of per capita GRDP, population, and labor force participation rate (TPAK) on poverty in 10 provinces on Sumatra Island during the 2019–2023 period from an Islamic economic perspective. The data used in this study are panel data sourced from the Central Statistics Agency (BPS), and analyzed using a quantitative approach with the selected regression model, the Fixed Effect Model (FEM). Data analysis using EViews 10 software. The results of this study indicate that partially GRDP per capita has a negative and insignificant effect on poverty in 10 Provinces of Sumatra Island, with a coefficient value of -0.000834 and a probability of 0.6233 (> 0.05), and Labor Force Participation Rate has a negative and insignificant effect on poverty in 10 Provinces of Sumatra Island with a coefficient value of -1.669434 and a probability of 0.6618 (> 0.05), while population has a negative and significant effect on poverty in 10 Provinces of Sumatra Island with a coefficient value of -0.057793 and a probability of 0.0047 (< 0.05). Simultaneously, GRDP per capita, population, and labor force participation rate together have a significant effect on poverty in 10 Provinces of Sumatra Island with an f-statistic value of 1716.848 and an f-statistic probability of 0.000000 (< 0,05). From an Islamic economic perspective, poverty alleviation efforts must also incorporate principles of justice, such as zakat and waqf. These findings provide useful insights for policymakers in formulating effective strategies to improve public welfare.